Current Applications and Development of Radiomics in Osteoporosis: A Narrative Review - Shuyu Liu; He Gong; Peipei Shi; Chenchen Li; Qi Zhang; Jinming Zhang (Applied Sciences)
Osteoporosis is a prevalent disease among the elderly, with fractures being one of the most serious consequences. Early diagnosis and accurate assessment of fracture risk could help prevent fractures. Radiomics employs advanced image analysis techniques for the development of diagnostic tools, thereby improving the accuracy of disease diagnosis and treatment strategies. Specifically, in the application of bone diseases, radiomics has proven effective in the diagnosis and prognostic evaluation of osteoporosis, osteoarthritis, and bone tumors. Radiomics allowed for quantitative characterization of bone geometry, material distribution, and microstructure, making it applicable to osteoporosis as well. In this review, an overview was provided regarding the current progress of radiomics based on clinical bone imaging in osteoporosis, including bone strength assessment, osteoporosis diagnosis, and fracture risk prediction. Additionally, the potential and challenges for their clinical application were summarized.